Spatial distribution of convective clouds over Madras and neighbourhood (MAUSAM, 1982)
Spatial distribution of convective clouds as seen in PPI-scope recorded at Madras in the Decca-4l radar for the characteristic months viz., April, June and September 1978 are presented. Also the spatial distribution (diurnal variation) of echoes over land and sea during the three different parts of the day for April. June and September for the year 1978 are also presented.